Using Physics Education Technology as Virtual Laboratory in Learning Waves and Sounds - Shopi Setiawati Maulidah; Eka Cahya Prima (Journal of Science Learning, 2018)
This research was intended to analyze the use of Physics Education Technology (PhET) as a virtual laboratory in learning waves and sounds. The analysis was in terms of the implementation of waves on a string student activity as a lesson plan, the profile of students’ cognitive, and the profile of science laboratory environment. The method which is used in this research was a descriptive method with methodological triangulation as the research design. The sample was taken on the convenient situation at grade 8 in an international school in Bandung. According to the analysis of the result, the waves on a string student activity can be adopted as the lesson plan with several recommendation to be improved such as in part A, changing some sentences in the data table, changing some settings in obtaining data activity, and adding clear example in determining the base and peak point in measuring the height of wave at start and at the end. Moreover in part B, adding clear instruction on how to use the ruler to measure the wavelength, and changing the picture to obtain the data of wavelength with the picture of simulation with the instructed setting are important. In part C, it needs to add the instruction to do the practice session together with the teacher and to add the instruction to make the starting point in counting the wave similar in each trial. The use of Physics Education Technology (PhET) as a virtual laboratory in learning waves and sounds shows the favorable result on both the cognitive aspect and science laboratory environment.